the first step is to let f(x)=g(x)
-x^2-2x+6=2x^2+5x+3
we will have the following equation, i moved all the variables on the left side so we will have just one equation
-x^2-2x^2-2x-5x+6-3=0
-3x^2-7x+3=0
we will solve this equation using the quadratic formula
the roots, x1= -2.7, x2= 0.369
your choice are a)=-2.7 and if we round up, d)=0.4
![\begin{gathered} x1,2=(-b+-\sqrt[]{b^2-4ac})\frac{}{} \\ \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r9ym3tcftql112z0ttgx14lg8raw19sbv4.png)
all divided by 2a